Impact Of Gamification On Intention To Donate Using Crowdfunding Platform: Evaluating The Mediating Roles Of Affective User Experience And Trust - Nur Aqilah Hazirah Mohd Anim; Nor Asiah Omar; Xin-Jean Lim; Wan Rasyidah Wan Nawang; Syed Shah Alam (Faculty of Business and Economics, University of M, 2024)
Indexed by ERA/MyCite